Kapok fiber loaded manganese-vanadium-based phosphate composite material as well as preparation method and application thereof

By uniformly attaching manganese vanadium-based phosphate on kapok fibers, the structural distortion and electrochemical performance attenuation caused by volume changes in the charging and discharge process of sodium ion battery positive electrode materials are solved, and high conductivity and excellent electrochemical stability are achieved. Composite materials improve the performance of sodium ion batteries.

CN119503769APending Publication Date: 2025-02-25WUHAN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411635296.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have structural distortions due to volume changes during charging and discharging, and the electrochemical performance is attenuated, and the conductivity is low, which limits its practical application.

Method used

Using kapok fibers as biological carbon source and templates, adsorbs the precursor solution through the hollow structures in it, and using ammonia diffusion, manganese vanadium-based phosphate is uniformly attached to the inner and/or outer walls of kapok fibers to prepare a composite with high conductivity. Material.

Benefits of technology

The composite material exhibits excellent structural stability and electrochemical stability, improves the reversible specific capacity of sodium ion batteries, and effectively alleviates the volume changes of the positive electrode material during inlaidation/desodiumization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503769A_ABST
    Figure CN119503769A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and discloses a kapok fiber loaded manganese-vanadium-based phosphate composite material as well as a preparation method and application thereof. The preparation method comprises the following steps: 1) carrying out hydrophilic treatment on the kapok fibers; 2) preparing a precursor solution; 3) adding the kawo kawo fibers subjected to hydrophilization treatment into the precursor solution for soaking, taking out the kawo kawo fibers, placing the kawo kawo fibers on a breathable mesh material, and enabling the kawo kawo fibers to be fully exposed in ammonia gas for reaction to obtain precursor powder; and 4) sintering the precursor powder in an inert atmosphere to obtain the kapok fiber loaded manganese-vanadium-based phosphate composite material. The kapok fiber is used as a biological carbon source and a template, the hollow structure of the kapok fiber is used for adsorbing the precursor solution, then the manganese-vanadium-based phosphate is uniformly loaded on the inner wall and / or the outer wall of the kapok fiber tube through the diffusion effect of ammonia gas, and the obtained composite material is high in conductivity and can be used as a sodium ion battery positive electrode active material. Excellent structural stability and electrochemical stability are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy materials, and specifically relates to a kapok fiber-loaded manganese-vanadium-based phosphate composite material and a preparation method and application thereof. Background Art

[0002] In today's society, fossil energy is non-renewable and the environmental problems it causes seriously affect the sustainable development of society, so the demand for new energy materials is increasing. As an outstanding representative of new energy materials, secondary energy storage batteries are widely used due to their unique advantages, such as low cost, high energy density, and long cycle life. Compared with lithium-ion batteries, sodium-ion batteries have abundant raw material reserves, wide distribution, and low cost, and have attracted widespread attention. However, due to the + The radius is much larger than Li + The radius, ion diffusion kinetics are slow, and the volume change caused during the charge and discharge process is large, which causes the structure to be distorted and leads to the attenuation of the electrochemical performance of the material. Therefore, the preparation of sodium ion battery positive electrode materials with excellent structure and electrochemical performance is the most difficult research problem that should be solved at present.

[0003] Sodium superion conductor (NASICON) type polyanion phosphate Na4Mn x V 2-x (PO4)3 is recognized as one of the most promising sodium ion cathode materials due to its three-dimensional framework structure, fast ion diffusion path, high voltage and energy density, high safety and low cost. However, this type of material also has problems such as low conductivity and large volume change during sodium insertion and extraction, which limits its practical application. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a kapok fiber-loaded manganese vanadium-based phosphate composite material and a preparation method and application thereof in view of the deficiencies in the prior art. The kapok fiber is used as a biocarbon source and template, and its hollow structure is utilized to adsorb a precursor solution, and then the manganese vanadium-based phosphate is uniformly loaded on the inner wall and / or outer wall of the kapok fiber tube through the diffusion effect of ammonia gas. The obtained composite material has high electrical conductivity and is used as a positive electrode active material for sodium ion batteries, showing excellent structural stability and electrochemical stability.

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a method for preparing a kapok fiber-loaded manganese-vanadium-based phosphate composite material, comprising the following steps:

[0006] 1) Carrying out hydrophilization treatment on kapok fibers;

[0007] 2) adding a sodium source, a vanadium source, a manganese source, a phosphorus source, and a complexing agent into water and mixing them evenly to obtain a uniform precursor solution without precipitation;

[0008] 3) adding the hydrophilized kapok fibers into the precursor solution and soaking them, taking them out and placing them on a breathable mesh material to fully expose them to ammonia gas for reaction, drying and grinding them after the reaction to obtain precursor powder;

[0009] 4) The precursor powder is sintered in an inert atmosphere, and ground after cooling to obtain a kapok fiber-loaded manganese-vanadium-based phosphate composite material.

[0010] In the above scheme, the hydrophilization treatment is one of acid-base treatment and carbonization treatment.

[0011] Furthermore, the acid-base treatment step includes: soaking the kapok fiber in a sodium hydroxide solution first, then soaking it in hydrochloric acid, taking it out, washing it, and drying it.

[0012] Furthermore, the concentration of the sodium hydroxide solution is 0.5 to 1 mol / L, and the soaking time is 12 to 24 hours.

[0013] Furthermore, the concentration of the hydrochloric acid is 0.5 to 1 mol / L, and the soaking time is 0.5 to 2 hours.

[0014] Furthermore, the carbonization treatment step includes: heating the kapok fiber for carbonization under the protection of an inert gas, the carbonization temperature is 350 to 550° C., and the heat preservation time is 2 to 6 hours.

[0015] In the above scheme, the sodium source is at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, and sodium acetate.

[0016] In the above scheme, the vanadium source is at least one of ammonium metavanadate and vanadium chloride.

[0017] In the above scheme, the manganese source is at least one of manganese carbonate, manganese acetate, manganese nitrate and manganese oxalate.

[0018] In the above scheme, the phosphorus source is at least one of diammonium phosphate, ammonium phosphate, sodium dihydrogen phosphate, and phosphoric acid.

[0019] In the above scheme, the complexing agent is at least one of glucose, starch, sucrose and citric acid.

[0020] In the above scheme, the ratio of the amount of the sodium source, vanadium source, manganese source, phosphorus source and complexing agent is 4:x:(2-x):3:(1-4), 0<x<2.

[0021] In the above scheme, in step 2), the volume ratio of the amount of the sodium source substance to water is 0.01 mol: (20-50) mL.

[0022] In the above scheme, the length of the kapok fibers after the hydrophilization treatment is 1 to 5 mm.

[0023] In the above scheme, the ratio of the mass of the kapok fiber after the hydrophilization treatment to the total amount of manganese and vanadium elements in the precursor solution is (0.05-1) g:0.01 mol.

[0024] In the above scheme, the kapok fibers after the hydrophilization treatment are immersed in the precursor solution for 5 to 10 minutes.

[0025] In the above scheme, the reaction time of the hydrophilized kapok fibers and ammonia is 1 to 5 minutes.

[0026] In the above scheme, in step 3), the drying is a two-stage drying, first heating to evaporate the solvent, and then fully drying.

[0027] Furthermore, the heating temperature of the heating evaporation is 80-85° C., and the heating time is 2-6 hours.

[0028] Furthermore, the drying temperature of the sufficient drying is 120-150° C., and the drying time is 2-4 hours.

[0029] In the above solution, the particle size of the precursor powder is 1 to 3 μm.

[0030] In the above scheme, the inert atmosphere is one of argon and nitrogen.

[0031] In the above scheme, the sintering treatment steps include: first heating to 350-400° C. and keeping the temperature for 2-6 hours, and then heating to 550-750° C. and keeping the temperature for 8-12 hours.

[0032] Furthermore, the heating rate is 2 to 5°C / min.

[0033] The invention also provides a kapok fiber-loaded manganese-vanadium-based phosphate composite material, which is prepared by the above method.

[0034] In the above scheme, the chemical formula of the composite material is Na4Mn x V 2-x (PO4)3 / C, 0<x<2.

[0035] In the above scheme, the microscopic morphology of the composite material includes a hollow tubular structure of kapok fibers and manganese-vanadium-based phosphate flaky particles attached to the inner wall and / or outer wall of the hollow tubular structure, wherein the diameter of the flaky particles is 200-500 nm.

[0036] The present invention also provides an application of a kapok fiber-supported manganese-vanadium-based phosphate composite material in a sodium ion battery, which is used as a positive electrode active material of the sodium ion battery to prepare the sodium ion battery.

[0037] In the above scheme, the specific application method is: the composite material is mixed with the conductive agent and the binder to form a slurry, coated on the aluminum foil current collector, and used as the positive electrode of the sodium ion battery after drying, and assembled into a sodium ion battery together with the negative electrode, separator and electrolyte of the sodium ion battery.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The invention makes full use of natural biomass material kapok fiber, which is rich in raw materials, low in price and environmentally friendly. The kapok fiber is used as a biological carbon source and template, and its unique hollow tubular structure is used to adsorb a precursor solution. Then, through the diffusion effect of ammonia gas, manganese vanadium-based phosphate is uniformly precipitated and attached to the inner wall and / or outer wall of the kapok fiber, thereby reducing the agglomeration of particles and preparing a composite material with a specific morphology and uniform particle distribution. The composite material is used as a positive electrode active material for a sodium ion battery and exhibits excellent structural stability and electrochemical stability. On the one hand, through the inheritance of carbon elements, synthetic biological residual carbon materials are introduced into the manganese vanadium-based phosphate to increase the conductivity of the material. On the other hand, the tubular structure of the kapok fiber is well maintained after carbonization, which can shorten the ion diffusion path, provide a channel for the rapid transmission of the electrolyte, and effectively alleviate the volume change of the positive electrode material during the insertion / extraction of sodium, enhance the interaction with sodium ions, and improve the reversible specific capacity of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a SEM image of the kapok fiber-loaded manganese-vanadium-based phosphate composite material prepared in Example 1.

[0041] Figure 2 This is a SEM image of the kapok fiber-loaded manganese-vanadium-based phosphate composite material prepared in Example 2.

[0042] Figure 3 This is the SEM image of the sodium manganese vanadium phosphate material prepared in Comparative Example 1.

[0043] Figure 4 This is the SEM image of the sodium manganese vanadium phosphate material prepared in Comparative Example 2.

[0044] Figure 5 The XRD patterns of the materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 are shown.

[0045] Figure 6 The cycling performance diagram of CR2032 button-type half-cells assembled with the materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 as positive electrode active materials of sodium ion batteries at 0.5C.

[0046] Figure 7The capacities and charge-discharge curves of CR2032 button half-cells assembled with the materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 as positive electrode active materials of sodium ion batteries at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C and 0.1C. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] Example 1

[0049] This embodiment provides a method for preparing a kapok fiber-supported manganese-vanadium-based phosphate composite material Na4MnV(PO4)3 / C, comprising the following steps:

[0050] 1) soaking the kapok fiber in a 0.5 mol / L sodium hydroxide solution for 24 h, then soaking it in a 0.5 mol / L hydrochloric acid solution for 0.5 h, taking it out and rinsing it with deionized water, and drying it in an oven at 80° C. for 1 h to obtain the hydrophilized kapok fiber;

[0051] 2) Add 20 mmol sodium acetate, 5 mmol ammonium metavanadate, 5 mmol manganese acetate, 15 mmol ammonium dihydrogen phosphate, and 15 mmol citric acid into 50 mL deionized water and mix well to obtain a uniform precursor solution without precipitation;

[0052] 3) Cut the kapok fiber after hydrophilization into small segments of 1 to 5 mm, then take 0.1 g and add it to the above precursor solution to soak for 5 minutes, take it out and place it on the nickel foam, and place ammonia water under the nickel foam. The ammonia gas volatilized by the ammonia water passes through the nickel foam and reacts with the precursor solution on the inner wall and / or outer wall of the kapok fiber. The reaction time is 2 minutes. After the reaction is completed, heat and stir in a water bath at 80°C for 2 hours to evaporate the solvent to obtain a gel, and then place the gel in a 150°C forced air drying oven to fully dry for 4 hours, and then grind it into powder in a mortar to obtain a precursor powder with a particle size of 1 to 3 μm;

[0053] 4) The precursor powder was placed in a muffle furnace under an argon atmosphere, first heated to 350°C at a rate of 5°C / min and kept at that temperature for 4 hours, then heated to 700°C at a rate of 5°C / min and kept at that temperature for 10 hours, then naturally cooled and ground to obtain Na4MnV(PO4)3 / C with a particle size of 0.5-2μm.

[0054] Example 2

[0055] This embodiment provides a kapok fiber-supported manganese-vanadium-based phosphate composite material Na4Mn1.2 V 0.8 The preparation method of (PO4)3 / C comprises the following steps:

[0056] 1) Cut the kapok fibers into small segments of 1 to 5 mm, put them into a muffle furnace, and carbonize them at 500°C for 3 h under the protection of argon atmosphere, with a heating rate of 5°C / min, and then cool them naturally to obtain hydrophilized kapok fibers;

[0057] 2) Add 20 mmol sodium acetate, 4 mmol ammonium metavanadate, 5 mmol manganese acetate, 15 mmol ammonium dihydrogen phosphate, and 10 mmol citric acid into 50 mL deionized water and mix well to obtain a uniform precursor solution without precipitation;

[0058] 3) 0.2 g of the hydrophilized kapok fiber was added to the precursor solution and soaked for 10 min. After being taken out, it was placed on the nickel foam, and ammonia water was placed under the nickel foam. The ammonia gas volatilized by the ammonia water permeated the nickel foam and reacted with the precursor solution on the inner wall and / or outer wall of the kapok fiber. The reaction time was 2 min. After the reaction was completed, it was heated and stirred in a water bath at 80° C. for 4 h to evaporate the solvent to obtain a gel. The gel was then placed in a 150° C. forced air drying oven and fully dried for 2 h. It was then ground into powder in a mortar to obtain a precursor powder with a particle size of 1 to 3 μm.

[0059] 4) The precursor powder was placed in a muffle furnace under an argon atmosphere, first heated to 400°C at a rate of 5°C / min and kept at that temperature for 2 h, then heated to 600°C at a rate of 5°C / min and kept at that temperature for 12 h, then cooled naturally and ground to obtain Na4Mn with a particle size of 0.5 to 2 μm. 1.2 V 0.8 (PO4)3 / C.

[0060] Comparative Example 1

[0061] Comparative Example 1 is Na4MnV(PO4)3, and its preparation method is:

[0062] 1) Add 20 mmol sodium acetate, 5 mmol ammonium metavanadate, 5 mmol manganese acetate, 15 mmol ammonium dihydrogen phosphate, and 15 mol citric acid into 50 mL deionized water and mix well to obtain a uniform precursor solution without precipitation;

[0063] 2) The precursor solution was heated and stirred in a water bath at 80°C for 2 hours to evaporate the solvent to obtain a gel, and then the gel was placed in a 150°C forced air drying oven to be fully dried for 4 hours, and then ground into powder in a mortar to obtain a precursor powder with a particle size of 1 to 3 μm;

[0064] 3) The precursor powder was placed in a muffle furnace under an argon atmosphere, first heated to 350°C at a rate of 5°C / min and kept at this temperature for 4 hours, then heated to 700°C at a rate of 5°C / min and kept at this temperature for 10 hours, then naturally cooled and ground to obtain Na4MnV(PO4)3 / C with a particle size of 0.5-1 μm.

[0065] Comparative Example 2

[0066] Comparative Example 2 is Na4Mn 1.2 V 0.8 (PO4)3 / C, the preparation method thereof is:

[0067] 1) Add 20 mmol sodium acetate, 4 mmol ammonium metavanadate, 5 mmol manganese acetate, 15 mmol ammonium dihydrogen phosphate, and 10 mmol citric acid to 50 mL deionized water and mix well to obtain a uniform precursor solution without precipitation;

[0068] 2) Cut the untreated kapok fiber into small segments of 1 to 5 mm, then take 0.2 g and add it to 15 mL of anhydrous ethanol, and then add it to the above precursor solution to obtain a mixed solution;

[0069] 3) The mixed solution was heated and stirred in a water bath at 80°C for 4 hours to evaporate the solvent to obtain a gel, and then the gel was placed in a 150°C forced air drying oven to be fully dried for 2 hours, and then ground into powder in a mortar to obtain a precursor powder with a particle size of 1 to 3 μm;

[0070] 4) The precursor powder was placed in a muffle furnace under an argon atmosphere, first heated to 400°C at a rate of 5°C / min and kept at that temperature for 2 h, then heated to 600°C at a rate of 5°C / min and kept at that temperature for 12 h, then cooled naturally and ground to obtain Na4Mn with a particle size of 0.5 to 2 μm. 1.2 V 0.8 (PO4)3 / C.

[0071] The materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were tested and analyzed using a scanning electron microscope (SEM). The test results are shown in the attached figure. Figures 1 to 4 shown. Figures 1-2 It can be seen that after high temperature treatment, the tubular structure of kapok fiber can be basically maintained, Na4Mn x V 2-x (PO4)3 material is evenly distributed in the material in the form of flakes, with a particle diameter of 200 to 500 nm. The hollow tubular structure can make Na4Mn x V 2-x The (PO4)3 material is uniformly attached to the inner wall and / or outer wall of the kapok fiber. Figure 3It can be seen that the Na4MnV(PO4)3 material prepared in Comparative Example 1 is evenly distributed in the form of flakes, and the particle diameter is still 200-500nm. Figure 4 It can be seen that the Na4Mn prepared in Comparative Example 2 1.2 V 0.8 In (PO4)3 / C, there is almost no Na4Mn attached to the kapok fiber 1.2 V 0.8 (PO4)3 particles, Na4Mn 1.2 V 0.8 (PO4)3 material particles showed obvious agglomeration.

[0072] The materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were tested and analyzed using an X-ray diffractometer (XRD). The test results are shown in the attached figure. Figure 5 As shown in the figure, all the diffraction peaks of the material samples can prove that they have The space group is NASICON diamond structure (JCPDS 98-042-3538), without any impurity peaks, indicating that the introduction of kapok fiber exists only as a carbon source.

[0073] The materials obtained in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were respectively used as positive electrode active materials of sodium ion batteries to prepare sodium ion batteries, and the specific steps were as follows:

[0074] Example 1 (Example 2, Comparative Example 1, Comparative Example 2), acetylene black, and PVDF were added to a mortar at a mass ratio of 8:1:1 and ground to mix them evenly. Then, an appropriate amount of N-methylpyrrolidone (NMP) was added to make a uniform slurry, and evenly coated on an aluminum foil to obtain a working electrode. Dry in an oven at 80°C for 2 hours, and cut into positive electrode discs with a diameter of 14 mm. After weighing, put them in a vacuum drying oven and keep them warm at 120°C for 12 hours. Use a metal sodium sheet as the counter electrode, glass fiber as the diaphragm, 1 mol / L NaPF6 / DIG (diethylene glycol dimethyl ether) as the electrolyte, and the prepared electrode pole piece as the working electrode, which is assembled into a CR2032 button half-cell in a glove box under argon atmosphere protection.

[0075] Constant current charge and discharge tests were performed on the battery detection system (NEWARE) with a voltage window of 2.5 to 3.8V. Figure 6 The results show that the battery assembled with the positive electrode materials described in Example 1 and Example 2 has a discharge capacity of 106.68 and 105.85 mAh g at 0.1C. -1 , which is much larger than the discharge capacity of Comparative Examples 1 and 2 (85.57 mAh g -1 and 92.11mAh g -1). And the capacity retention rate of Example 1 and Example 2 after 100 cycles is as high as 94.02% and 89.66%, respectively, which has excellent long cycle performance. This shows that the introduction of kapok fiber has an excellent effect on the Na4Mn x V 2-x The (PO4)3 material plays a good buffering role and can effectively cope with the huge volume changes during the sodium insertion and extraction process, thereby ensuring the stability of the electrode material.

[0076] The rate performance test was performed on the battery detection system (NEWARE) with a voltage window of 2.5 to 3.8V. Figure 7 The results show that the batteries assembled with the positive electrode materials described in Example 1 and Example 2 can still maintain 85.96 and 80.71 mAh g at 10C. -1 The discharge capacity is much larger than that of Comparative Example 1 and Comparative Example 2 (60.14 mAh g -1 、65.51mAh g -1 ); and when the current density returns to 0.1C, the capacity retention rates of the batteries assembled with the positive electrode materials described in Examples 1 and 2 are 98.92% and 93.58%, while the capacity retention rates of the batteries assembled with the positive electrode materials described in Comparative Examples 1 and 2 are 91.97% and 91.95%. It can be seen that the positive electrode materials described in Examples 1 and 2 have excellent rate performance. The material has good stability.

[0077] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A method for preparing a kapok fiber-supported manganese-vanadium-based phosphate composite material, characterized in that: The following steps are involved: 1) Carrying out hydrophilization treatment on kapok fibers; 2) adding a sodium source, a vanadium source, a manganese source, a phosphorus source, and a complexing agent into water and mixing them uniformly to obtain a uniform precursor solution without precipitation; 3) adding the hydrophilized kapok fibers into the precursor solution and soaking them, taking them out and placing them on a breathable mesh material to fully expose them to ammonia gas for reaction, drying and grinding them after the reaction to obtain precursor powder; 4) The precursor powder is sintered in an inert atmosphere, and ground after cooling to obtain a kapok fiber-loaded manganese-vanadium-based phosphate composite material.

2. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: The hydrophilization treatment is an acid-base treatment, and the steps include: soaking the kapok fiber in a sodium hydroxide solution first, and then soaking it in hydrochloric acid, taking it out, washing it, and drying it; the concentration of the sodium hydroxide solution is 0.5-1 mol / L, and the soaking time is 12-24 hours; the concentration of the hydrochloric acid is 0.5-1 mol / L, and the soaking time is 0.5-2 hours.

3. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: The hydrophilization treatment is a carbonization treatment, and the steps include: heating the kapok fiber under the protection of an inert gas for carbonization, the carbonization temperature is 350-550° C., and the heat preservation time is 2-6 hours.

4. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: In step 2), the molar ratio of the sodium source, vanadium source, manganese source, phosphorus source and complexing agent is 4:x:(2-x):3:(1-4), 0<x<2, and the volume ratio of the molar ratio of the sodium source to water is 0.01 mol:(20-50) mL.

5. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: The length of the hydrophilized kapok fiber is 1 to 5 mm; the ratio of the mass of the hydrophilized kapok fiber to the total amount of manganese and vanadium elements in the precursor solution is (0.05 to 1) g:0.01 mol; the immersion time of the hydrophilized kapok fiber in the precursor solution is 5 to 10 min; the reaction time of the hydrophilized kapok fiber and ammonia is 1 to 5 min.

6. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: In step 3), the drying is a two-stage drying, first heating to evaporate the solvent, and then fully drying; the heating temperature of the heating evaporation is 80-85°C, and the heating time is 2-6h; the drying temperature of the fully drying is 120-150°C, and the drying time is 2-4h; the particle size of the precursor powder is 1-3μm.

7. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: The sintering treatment steps include: first heating to 350-400° C. and keeping the temperature for 2-6 hours, then heating to 550-750° C. and keeping the temperature for 8-12 hours; the heating rate is 2-5° C. / min.

8. The method for preparing the kapok fiber-supported manganese-vanadium-based phosphate composite material according to claim 1, characterized in that: The sodium source is at least one of sodium carbonate, sodium bicarbonate, sodium dihydrogen phosphate, and sodium acetate; the vanadium source is at least one of ammonium metavanadate and vanadium chloride; the manganese source is at least one of manganese carbonate, manganese acetate, manganese nitrate, and manganese oxalate; the phosphorus source is at least one of ammonium dihydrogen phosphate, ammonium phosphate, sodium dihydrogen phosphate, and phosphoric acid; and the complexing agent is at least one of glucose, starch, sucrose, and citric acid.

9. A kapok fiber-supported manganese-vanadium-based phosphate composite material prepared by the method of any one of claims 1 to 8, characterized in that: The chemical formula of the composite material is Na4Mn x V 2-x (PO4)3 / C, 0<x<2, its microstructure includes a hollow tubular structure of kapok fiber and manganese vanadium-based phosphate flaky particles attached to the inner wall and / or outer wall of the hollow tubular structure, wherein the diameter of the flaky particles is 200-500nm.

10. Use of the kapok fiber-supported manganese-vanadium-based phosphate composite material as claimed in claim 9 in sodium ion batteries.